2005
DOI: 10.1172/jci22681
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytes from Munc18c-null mice show increased sensitivity to insulin-stimulated GLUT4 externalization

Abstract: Insulin-stimulated glucose uptake in adipocytes is mediated by translocation of vesicles containing the glucose transporter GLUT4 from intracellular storage sites to the cell periphery and the subsequent fusion of these vesicles with the plasma membrane, resulting in the externalization of GLUT4. Fusion of the GLUT4-containing vesicles with the plasma membrane is mediated by a soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex consisting of vesicle-associated membrane protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
93
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 39 publications
9
93
2
Order By: Relevance
“…These data are consistent with studies of neural Munc18 knockouts and that of lower organisms [61,62]. However another study, found that homozygous Munc18c knockout mice were viable and had increased insulin sensitivity consistent with Munc18c actin as a fusogenic inhibitor [63]. Insulin has also been observed to induce the association of PKC and Munc18c concomitant with a dissociation of the syntaxin4/Munc18c complex [50].…”
Section: Glut4 Vesicle Docking and Plasma Membrane Fusionsupporting
confidence: 86%
“…These data are consistent with studies of neural Munc18 knockouts and that of lower organisms [61,62]. However another study, found that homozygous Munc18c knockout mice were viable and had increased insulin sensitivity consistent with Munc18c actin as a fusogenic inhibitor [63]. Insulin has also been observed to induce the association of PKC and Munc18c concomitant with a dissociation of the syntaxin4/Munc18c complex [50].…”
Section: Glut4 Vesicle Docking and Plasma Membrane Fusionsupporting
confidence: 86%
“…For example, the dissociation of yeast homologs Sly1p (Munc18 homolog) and Sed5p (syntaxin homolog) has been shown to require the small GTPase protein Ypt1p (66). Similarly, in adipocytes, the Munc18c-Syntaxin 4 complex has been proposed to be dissociated upon activation of the Rab4 GTPase (67) or the phosphatidylinositol 3-kinase/Akt-dependent phosphorylation the of Rab GTPase-activating protein AS160 (68,69). In support of this, the crystal structure of Munc18-1 revealed a region that is very similar to the Ypt1p-binding site of Sly1p (70).…”
Section: Discussionmentioning
confidence: 99%
“…To generate N-terminal fluoroprotein-labeled constructs, the following cDNAs were subcloned into the SalI-XbaI sites of pDNR-dual for use with the Cre recombinase-mediated Creator System (Clontech): rat Munc18a (pGex-KG-Munc18a), rat syntaxin 1A (pGEX-syntaxin 1A 11 ), rat Munc18c (pcDNA3-FLAG-Munc18c), human syntaxin 4 (pcDNA4/TO/syntaxin 4-Myc 2 -His), and human SNAP23 (pcDNA3-SNAP23) (gifts from J. Pevsner, R. Scheller, J. Pessin, and T. Weimbs (syntaxin 4 and SNAP23), respectively). The recipient vectors pLoxP-ECFP-C1 and pLoxP-EcYFP-C1 (Q39M mutant of pEYFP-C1; citrine) were generated and mutated to their monomeric forms (A206K) from pLoxP-EGFP-C1 (Clontech) as described previously (17).…”
Section: Methodsmentioning
confidence: 99%
“…Based on overexpression studies, Munc18c was initially proposed to function as a negative regulator of GLUT4 vesicle translocation in 3T3L1 adipocytes (5,6). Furthermore, the failure of the phosphatidylinositol 3-kinase inhibitor wortmannin to suppress GLUT4 externalization in adipocytes derived from Munc18c-null mice suggests that Munc18c inhibits docking and/or fusion under the control of the phosphatidylinositol 3-kinase pathway (11). Although the exact mechanism for this inhibition is not fully understood, Munc18c has been proposed to preclude the binding of syntaxin 4 to its cognate SNAREs, VAMP2 (vesicle-associated membrane protein 2) and SNAP23 (synaptosome-associated protein of 23 kDa), preventing GLUT4 externalization in the absence of insulin (5,6,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation